Communication Model in the Learning Process at Al-Fityan Elementary School in Gowa - Anas (Jurnal Mercusuar, 2023)
This research aims to analyze the communication model in the learning process at Al-Fityan Islamic Integrated Elementary School (SDIT) in Gowa. Data was collected through observation, interviews, and document studies. The data analysis method used the Miles and Huberman interactive model, which involves data collection, data reduction, data display, and verification. The results of the study show that the communication model used by SDIT Al-Fityan Gowa is interactive and dialogical, where teachers and students share knowledge and experiences. This communication model functions to enhance learning effectiveness and helps students better understand the concepts being taught. The use of supporting media and technology, such as online learning applications and other teaching aids, also plays an important role in this communication process. Furthermore, this study also indicates that the communication model used by SDIT Al-Fityan Gowa can assist students in developing critical and creative thinking skills. In addition, this communication model can help students in improving their social and emotional skills. Overall, this research demonstrates that the communication model used by SDIT Al-Fityan Gowa is very effective in assisting students in the learning process. Therefore, this study suggests that this communication model can be adopted by other schools to improve learning effectiveness.